Components of plant species diversity along environmental gradients at various spatial scales in wetland environments of southern Africa. (13th December 2021) - Sieben, Erwin J.J.; Subbiah, Ashley; Job, Nancy; Chatanga, Peter; Collins, Nacelle; Corry, Fynn T.H.
Abstract: Questions: Effective conservation planning of wetlands requires an understanding of the drivers of wetland diversity at different spatial scales. This study addresses the question: which environmental variables are most responsible for the turnover of wetland plant diversity at various spatial scales (beta and gamma diversity)? Additionally, how does alpha diversity, which expresses the diversity on a local level, compare between different wetland habitats? Location: South Africa and Lesotho. Methods: Variation in wetland vegetation along environmental gradients was studied using an existing data set consisting of 1, 113 vegetation plots. Plant species composition was analyzed at three spatial scales using gradient analysis. Scale 1 represents a broad geographic scale, Scale 2 represents variation within a single catchment and Scale 3 represents variation within a single wetland. Shannon's Diversity and Evenness as proxies of alpha diversity were determined for five categories of wetland habitats. Results: The most important factors at the geographic scale were latitude, base level of the catchment, temperature, climate and underlying parent material. At the catchment scale, altitude, hydrogeomorphic type and topographic location were the most influential factors, while soil texture, sodium content, organic carbon content, wetness and electric conductivity played a major role at the wetland scale. At the national level, the most important spatial scale was the geographic scale, the second was the catchment and the third was the wetland scale. Although there was a wide range of variation in Shannon's Diversity Index between the different wetland habitats, the differences were significant for all categories. Conclusions: The results show that factors that play a major role in influencing plant diversity in wetlands are scale‐dependent. This indicates the importance of considering all three spatial scales in the conservation planning of wetlands in southern Africa, especially given the many different threats that wetlands face, including climate change. Abstract : A data set of 1, 113 wetland vegetation plots was subjected to variation partitioning in partial canonical analysis. Three spatial scales were recognized and most variation was explained by the geographic scale, followed by the catchment scale and lastly by the scale of the individual wetland. This will play an important role in conservation planning.